The Effect of Price and Location on Boarding Room Rental Decisions (Case Study on Students Who Rent Boarding Rooms In Adam Malik Km. 9) - Mardhiyah Dwi Ilhami; Yusan Feri (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of price on the decision to choose to rent a boarding room in the Adam Malik area km.9, to determine the effect of location on the decision to choose to rent a boarding room in the Adam Malik area km.9 and to determine the effect of price and location on the decision to choose a rental. boarding house in the adam malik area km.9. This research is a type of quantitative research. Data collection techniques using a questionnaire. Data analysis techniques used descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the results of the study it can be concluded that: Price (X1) has a positive and significant effect on rental decisions (Y) in boarding rooms in the Adam Malik Km area. 9. Location (X2) influences the decision to rent (Y) in boarding rooms in the Adam Malik Km area. 9. Price (X1) and location (X2) affect the decision to rent (Y) in boarding rooms in the Adam Malik Km area. 9.